The exosome component Rrp6 is required for RNA polymerase II termination at specific targets of the Nrd1-Nab3 pathway. - Melanie J Fox (PLoS Genetics, 2015)
The exosome and its nuclear specific subunit Rrp6 form a 3'-5' exonuclease complex that regulates diverse aspects of RNA biology including 3' end processing and degradation of a variety of noncoding RNAs (ncRNAs) and unstable transcripts. Known targets of the nuclear exosome include short (<1000 bp) RNAPII transcripts such as small noncoding RNAs (snRNAs), cryptic unstable transcripts (CUTs), and some stable unannotated transcripts (SUTs) that are terminated by an Nrd1, Nab3, and Sen1 (NNS) dependent mechanism. NNS-dependent termination is coupled to RNA 3' end processing and/or degradation by the Rrp6/exosome in yeast. Recent work suggests Nrd1 is necessary for transcriptome surveillance, regulating promoter directionality and suppressing antisense transcription independently of, or prior to, Rrp6 activity. It remains unclear whether Rrp6 is directly involved in termination; however, Rrp6 has been implicated in the 3' end processing and degradation of ncRNA transcripts including CUTs. To determine the role of Rrp6 in NNS termination globally, we performed RNA sequencing (RNA-Seq) on total RNA and perform ChIP-exo analysis of RNA Polymerase II (RNAPII) localization. Deletion of RRP6 promotes hyper-elongation of multiple NNS-dependent transcripts resulting from both improperly processed 3' RNA ends and faulty transcript termination at specific target genes. The defects in RNAPII termination cause transcriptome-wide changes in mRNA expression through transcription interference and/or antisense repression, similar to previously reported effects of depleting Nrd1 from the nucleus. Elongated transcripts were identified within all classes of known NNS targets with the largest changes in transcription termination occurring at CUTs. Interestingly, the extended transcripts that we have detected in our studies show remarkable similarity to Nrd1-unterminated transcripts at many locations, suggesting that Rrp6 acts with the NNS complex globally to promote transcription termination in addition to 3' end RNA processing and/or degradation at specific targets.